(untitled) (Docentes 2.0 Journal, 2023)
A historically neglected pillar of society is education. The difficulty faced by Peruvian universities manifests in various ways, including limited funding transfers, low academic standards, low quality of research, and lack of interest in developing collegiate social responsibility projects. This study aimed to identify the relationship between the quality of educational services and student satisfaction in virtualized or adapted courses at a public university in Peru in 2020. The research was based on the inductive and positivist paradigm, with a quantitative approach, non-experimental design, correlational type, and cross-sectional. The universe comprised 170 subjects, undergraduate students from the National Autonomous University of Alto Andina of Tarma. The technique collected information through a questionnaire on the quality of educational services and student satisfaction. The tests confirmed the presence of a significant correlation between the variables Quality of educational services and student satisfaction. The correlation identified was .790, classified as a considerable positive correlation; the associated probability is tr > t, p=.00<.05 (10> 1.654, p=.00<.05) so this correlation is significant. In conclusion, poor service quality is related to low student satisfaction. The same is true with the good and high level.